Serum Heat Shock Protein Levels and the Relationship of Heat Shock Proteins with Various Parameters in Chronic Obstructive Pulmonary Disease Patients - Unver, Ramazan; Deveci, Figen; Kirkil, Gamze; Telo, Selda; Kaman, Dilara; Kuluozturk, Mutlu (Aves, 2016)
OBJECTIVES: Chronic Obstructive Pulmonary Disease (COPD) is accompanied by increased cellular stress and inflammation. Most of the Heat Shock Proteins (HSPs) have strong cytoprotective effects. The role of HSPs in COPD pathogenesis has not determined completely. We investigated the serum level of HSPs in COPD patients, smokers without COPD and healthy non-smoking controls. Also, we evaluated the relationship of HSPs with various parameters (inflammatory, oxidative, functional status, quality of life) in COPD patients. MATERIAL AND METHODS: The levels of stress protein (HSP27, HSP70, HSP60, HSP90, CyPA), interleukin-6, C-reactive protein and malondialdehyde were measured in 16 healthy non-smoker, 14 smokers without COPD and 50 patients with stable COPD. Pulmonary function tests (PFT) and arterial blood gases parameters were measured. Health Related Quality of Life was evaluated and exercise capacity was measured with 6 minute walking test. RESULTS: Only HSP27 levels was significantly higher in COPD patients when compared with both healthy non-smoker and smokers without COPD (for both, p< 0.001). There was a weak-moderate negative correlation between serum levels of HSP27 and PFT parameters and between HSP27 levels and PaO2. Serum levels of HSP27 showed a weak-moderate positive correlation with symptom, activity and total scores. Subjects evaluated only smokers without COPD and patients with COPD; HSP27 had an area under the curve (AUC) in the receiver operating characteristic (ROC) curve of 0.819 (0.702-0.935; 95% CI; p= 0.000). CONCLUSION: Increased serum levels of HSP27 was found in COPD patients and our results showed sensitivity and specificity of serum HSP27 as diagnostic markers for COPD.
Keywords: COPD; heat shock protein; oxidative stress; hypoxia